The socio educational role of social institutions in reducing the phenomenon of sport bullying - بلقبي , فطوم; كتفي , ياسمينة (sports creativity, 2025)
Bullying is one of the popular social diseases at the present time , which has begun to expand its circle every day in its various forms ,types and manifestations of family bullying, school bullying, bullying of friends against each other,ports bullying and others, but in this article we will focus on sports bullying,this is because it has not received enough attention from the theroetical side because most researcheres focus on the types various types of bullying and denying sport bullying , and explaining the sport bullying theoretically is an urgent necessity to understand it deeply wich will helps to treat and reduce it ; the aim in this article is to categorize the socio educational role of various types of socio institutes from families , schools and so groups of comrads , and the media is reducing the phenomenon of sports bullying , an attempt to draw the attention to mediatically so provide the cures to this phenomenon enough to provide the uprising of a healthy individual social to a family member or school and all the social institutes ,and stand on the most important solutions and suggestions to limit the spread of this phenomenon in society and playgrounds in particular